2005
DOI: 10.1111/j.1523-1739.2005.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Rarity, Losses, and Risks for Native Fishes of the Lower Colorado River Basin: Implications for Conservation Listing

Abstract: We examined spatial distributions of fishes native to the lower basin of the Colorado River (25 species) at three scales to determine percent decline from historical distributions based on a regional biodiversity database. We cumulated records from 1843 to 1980 to develop a "historical distribution" for each species and used those occurrences recorded from 1981 to 1998 as "modern" records. We then contrasted historical and modern distributions to (1) quantify losses in spatial distribution; (2) determine how s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 42 publications
0
31
1
Order By: Relevance
“…Therefore, although movement was a possibility for all species present in the catchment (Fagan et al 2005), only spangled perch, bony bream, rainbowfish and glassfish were always found at the upstream sites, with silver tandan also occasionally present. We therefore suggest that these common and widespread species are the most likely to move the furthest during sporadic flooding in central Australia.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, although movement was a possibility for all species present in the catchment (Fagan et al 2005), only spangled perch, bony bream, rainbowfish and glassfish were always found at the upstream sites, with silver tandan also occasionally present. We therefore suggest that these common and widespread species are the most likely to move the furthest during sporadic flooding in central Australia.…”
Section: Discussionmentioning
confidence: 96%
“…Seven cyprinids in our study are endangered, four are threatened, one is of special concern and two are candidates for listing by the Endangered Species Act. On average, the range size of cyprinids has declined by greater than 30% since the 1950s (range: 214 to 100%; [20]), such that average occupancy for cyprinid species is just 15.4 km 2 in the basin [58]. Second, environmental conditions were already dramatically changed prior to the contemporary time period ( post-1980) used to characterize the fish communities, such that closely related species that may once have been locally adapted are no longer at an advantage.…”
Section: Discussionmentioning
confidence: 99%
“…However, during our researches, it was stated that not every species, no matter what category of extinction it belongs and the height of the extinction risk that category bears at the national and/or global level, is threatened Table 9 The relation between the global and national status of endangerment, the level of extinction risk, and the protection priorities of the aquatic species by the same and/or equal to that category, a danger of extinction in every habitat or the whole area it lives in. The problem of the assessment of the extinction risk of the endangered species is approached in different ways and among the ones that are more or less similar to our researches the results Fagan et al (2005) can be isolated. The author, as the base for the assessment of the risk use the data base (SONFISHES) with the qualitative and quantitative data of the ichthyofauna of the basin area of the Colorado river (U.S.A.) during the historically long (traditional) period of time as well as so called ''modern '' period, that is 1981-1998.…”
Section: Discussionmentioning
confidence: 88%